Haematological responses to repeated sprints in hypoxia across different sporting modalities. Issue 5 (3rd September 2022) - Camacho-Cardenosa, Marta; Camacho-Cardenosa, Alba; Kemp, Justin; Brazo-Sayavera, Javier; Timon, Rafael; Olcina, Guillermo
ABSTRACT: The aim was to determine the effects of repeated-sprint training in hypoxia on haematocrit and haemoglobin in different sporting modalities. Seventy-two participants were randomly allocated to Active-Repeated sprint in hypoxia (A-RSH, n= 8); Active-Repeated sprint in normoxia (A-RSN, n= 8); Active-Control (A-CON, n= 8); Team Sports-RSH (T-RSH, n= 8); Team Sports-RSN (T-RSN, n= 8); Team Sports-Control (T-CON, n= 8); Endurance-RSH (E-RSH, n= 8); Endurance-RSN (E-RSN, n= 8); Endurance-Control (E-CON, n= 8). Sessions consisted of two sets of five sprints of 10 swith recovery of 20 sbetween sprints and 10 min between sets. Blood samples for haematocrit and haemoglobin concentrations were obtained before and after, and 2 weeks after cessation. Haematocrit and haemoglobin were lower for the E-RSN group following 2 weeks of cessation of protocol compared with E-RSH (p = 0.035) and E-CON (p = 0.045). Haematocrit of the A-RSH group was higher compared with baseline (p = 0.05) and Post (p = 0.05). Similarly, the T-RSH group demonstrated increases in haematocrit following 2 weeks of cessation compared with Post (p = 0.04). Repeated Sprint Training in Hypoxia had different haematological effects depending on sporting modality.